2017
DOI: 10.1016/j.comppsych.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Mental disorder comorbidity and treatment utilization

Abstract: Objective Effective interventions have been developed for myriad common psychological and substance use disorders, though they remain highly underutilized. Previous research has shown that the likelihood of treatment utilization varies across disorder diagnosis. However, studies that focus on individual disorders have resulted in a large, piecemeal literature that neglects the high rates of multivariate comorbidity. The current study investigated the association between treatment utilization and transdiagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 92 publications
1
9
0
Order By: Relevance
“…The current findings extend those from the previous study on the associations between transdiagnostic factors and treatment access (Rodriguez-Seijas et al, 2017). In that study, the authors found that higher levels of the externalizing factor prevented individuals from accessing internalizing-related treatment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The current findings extend those from the previous study on the associations between transdiagnostic factors and treatment access (Rodriguez-Seijas et al, 2017). In that study, the authors found that higher levels of the externalizing factor prevented individuals from accessing internalizing-related treatment.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, disinhibition is associated with poor treatment response among those with substance use disorders (Chen et al, 2013; Mojtabai et al, 2002; Stevens et al, 2014). Further, disinhibition-related constructs—like the transdiagnostic externalizing factor (Rodriguez-Seijas, Eaton, Stohl, Mauro, & Hasin, 2017)—serve as impediments to accessing psychiatric intervention services.…”
Section: Discussionmentioning
confidence: 99%
“…First, community clinicians frequently do not select treatment according to diagnosis (Baldwin & Kosky, 2007; First et al, 2018; Hermes et al, 2013; Mohamed & Rosenheck, 2008; Taylor, 2016), instead they focus on symptoms and presenting complaints. Recent studies found that decision-making of community clinicians is more aligned with HiTOP description than with traditional diagnoses (Hopwood et al, 2019; Rodriguez-Seijas, Eaton, Stohl, Mauro, & Hasin, 2017; Waszczuk et al, 2017). Consequently, HiTOP can provide clinicians with normed, systematic tools to support their preferred practices more effectively than informal interviews on which many providers currently rely.…”
Section: Advantages and Limitations Of Hitop For Clinical Practicementioning
confidence: 99%
“…Also, research in the World Mental Health Surveys found that the persistence and new onset of DSM–IV diagnoses could be explained almost entirely by variation in higher-order internalizing and externalizing spectra (Kessler, Petukhova, & Zaslavsky, 2011; see also Kotov, Perlman, Gámez, & Watson, 2015). Regarding intervention, factor analytic studies in clinical samples suggest that treatment decisions by both practitioners (Waszczuk et al, 2017) and patients (Rodriguez-Seijas, Eaton, Stohl, Mauro, & Hasin, 2017) are based more on individual differences on higher-order dimensions (e.g., thought disorder) than DSM categories (e.g., schizotypal personality disorder). Thus, there are preliminary indications that dimensional assessment, especially at higher-order levels of the hierarchical framework, outperforms categorical assessment in forecasting key clinical outcomes (reviewed in Conway et al, in press).…”
Section: A Hierarchical Taxonomy Of Psychopathology (Hitop)mentioning
confidence: 99%